Augmented Reality for Chemistry Education: Systematic Literature Review (SLR) and Visualization - Setiawan, Riky; Santosa, Eka Budhi; Sukmawati, Fatma (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
The integration of immersive technologies into science education provides an innovative pathway for addressing abstract concepts, particularly within chemistry learning. This paper delivers a systematic review of literature concerning the integration of Augmented Reality (AR) in chemistry education, emphasizing molecular structure visualization and improved interactivity in learning processes. The review followed the PRISMA protocol, utilizing articles indexed in Scopus between 2020 and 2025. Out of 81 initial studies identified, ten satisfied the inclusion criteria and were further examined with bibliometric approaches. Findings highlight an increasing research focus on AR-based chemistry instruction, covering mobile learning, gamified environments, and molecular simulations. Major contributing countries included Germany, Switzerland, and Indonesia, with key subject domains spanning social sciences, computer science, and chemistry. Keyword mapping further indicates that AR is positioned as a pivotal element within the digital education landscape. These insights underline the transformative capacity of AR in redefining chemistry education toward a more flexible, interactive, and student-centered model.